Pour territorialiser les politiques publiques de l’eau potable : Prendre en compte le concernement territorial des acteurs et les configurations spatiales des dispositifs de gestion - Marion Charbonneau; Yves Poinsot (Cybergeo, 2018)
The adaptation of environmental public policies to the territories suffers from a vague conception of these. This paper studies the role of spatial entities, in their diversity of attributes, their contents, their scales and their forms, on the interactions among public policy’s stakeholders of the drinking water assets protection. The paper assesses situations where territorial conditions for the coordination of actors lead to success. It demonstrates that the territorial conditions for synergy on a medium-scale (supply entity of drinking water for tens of thousands of people) are gradually deteriorating. They lead to a concentration of water supply to a few major pumping places, the protection of which faces the demobilization of agricultural actors identified as polluters. Therefore, establishing short circuits for financing local public action constitutes a credible alternative to the use of the Agri-environment-climate Measures (AECM), which have poor social and political acceptability.